Peran Guru IPS Sebagai Motivator dalam Meningkatkan Minat Belajar Siswa Kelas VIII pada Mata Pelajaran IPS di MTSS Muhammadiyah Parumaan: Penelitian - Siti Jurriah; Mohamad Amir; Mohammad Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study focuses on describing the role of social studies teachers as motivators in fostering learning interest in eighth-grade students at MTSS Muhammadiyah Parumaan. Learning interest is an essential element that impacts learning outcomes, and teachers play a strategic role in fostering student enthusiasm and passion. This research employs a descriptive qualitative methodology; information is obtained through interviews, observations, and documentation reviews. Participants in this study consisted of social studies teachers, eighth-grade students, and school principals. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that social studies teachers actively act as motivators by implementing various strategies such as providing encouragement, creating a pleasant learning atmosphere, using varied learning methods, and utilizing technology. Teachers also involve students in discussions, provide rewards, support independent learning, and serve as good role models. Despite challenges such as low student motivation, teachers continue to strive to increase learning interest through creative approaches such as icebreakers and interactive quizzes. The role of the teacher as a motivator has been confirmed to be effective in optimizing the active involvement of students as well as their mastery of the substance of social studies lessons.